Los pueblos indígenas en el buen vivir global, un concepto como herramienta de inclusión de los excluidos - Philipp ALTMANN (Revista Iberoamericana de Estudios de Desarrollo)
Indigenous peoples have been and still are largely excluded from the most important areas of modern society. They cannot participate adequately in politics, economics, education, etc. This exclusion is linked to colonialism and the coloniality of power and manifests itself in the term «indigenous» itself. The indigenous movement, especially since the 1970s, showed a clear awareness of this contradiction. It took advantage of the oppressive categories in the sense of a collective liberation. The indigenous function as a mechanism of political inclusion allows a local movement to connect with other movements, insofar as they are linked to the indigenous. And the indigenous became a discursive vehicle for the central demands of indigenous movements worldwide. In this contribution, it will be discussed the internal and external effects of the dissemination of the buen vivir concept by the indigenous movement based on a deeper discussion of the mechanisms of self-inclusion sustained on the indigenous movements. The centre of this discussion will be the framed of the concrete demands of the indigenous movement, especially the Ecuadorian movement and its economic proposals, in the concept of buen vivir.